Lifestyle related to health and quality of life of girls at puberty in light of the KIDSCREEN-52 Questionnaire - Nowak-Starz, Grażyna; Zięba, Ewa (Medical Studies/Studia Medyczne, 2017)
Introduction : The lifestyle of every human being, to a large extent, determines their health. Whatever young individuals do in their adult lives is extremely important for themselves and the next generations. Aim of the research : To investigate the relationship between health-related lifestyle and the quality of life of girls in light of the KIDSCREEN-52 questionnaire. Material and methods: The study involved 122 girls with menstrual disorders from rural and urban areas and 240 girls without any health or developmental disorders. It was conducted on patients of the Public Gynaecological Clinic for Girls in Kielce and girls attending primary and middle schools. A diagnostic survey was used including the following research tools: KIDSCREEN-52 questionnaire, authors’ survey, body mass index, and Rohrer Index. Results: The quality of life and health of girls with menstrual disorders (group I) and girls without any health or development disorders (group II) both from rural and urban areas was assessed. Taking into account variables such as age and the living environment, it was stated that younger girls (13–14 years old) from groups I and II generally perceive their health as worse (p < 0.001). Whereas, among older girls in both groups I and II (15–16 years old), a larger percentage of respondents perceive themselves in a positive way, which results in higher self-assessment in health. Conclusions : The application of subjective health indicators in the assessment of quality of life relating to adolescence allows us to determine disease and malpractice in the care of the population in developmental age.